PENGEMBANGAN INSTRUMEN EVALUASI BERBASIS KEMAMPUAN PEMECAHAN MASALAH PADA MATERI EKSPONEN DI TINGKAT SMA - Rosyadi, M.; Yuhana, Yuyu (LPPM Universitas Bina Bangsa, 2024)
The purpose of this research is to produce a test instrument to measure mathematical problem-solving ability by looking at the development procedures and the quality of the mathematics problem solving instruments developed. The research used is the type of research (R&D) that is the development of test instruments to measure the ability to solve mathematical problems. The development model of this research instrument is developed on the basis of the Tessmer model which is the formative type of evaluation, i.e. (1) preliminary stage, (2) self evaluation stage, (3) prototyping stage (expert reviews, one-to-one and small group) and (4) field test stage. The test subject of the experiment were X Students of SMAN 2 Bayah which amounted to 25 students. Based on the results of experiments conducted, it is found that: (1) math problem solving test instrument has been said